Bursting the Bubble: A Case of Secondary Infertility - Wadhwani, Gyanda G.; Wadhwani, Parul G.; Sharma, Soma (Homœopathic Links, 2017)
Infertility has been a major medical and social preoccupation since the dawn of human existence and women have always been the symbol of fertility. A 34-year-old woman presented with inability to conceive for the past 2.5 years. A single dose of indicated homeopathic remedy helped her conceive during the following month. In contrast with the fertility specialists, homeopathic treatment addresses the entire underlying bio–psycho–social dimension under a single roof. Publication of a collective pooled data may help us establish this beyond doubt, for the benefit of incomplete families!
Keywords: Infertility; Vaginal flatulence; Lycopodium clavatum